FOLKLORE AMAQ SETOWEQ: SYSTEMIC FUNCTIONAL LINGUSITIC-BASED STUDY - Sudarianti, Sri (Warmadewa University, 2017)
Abstract This research is carried on to obtain the complete and comprehensive description about the Lombok Folklore Texs entitled Amaq Setoweq by using the SFL (Systemic Functional Linguistic) theory and make it relevant towards learning discourse analysis at college. The research emphasizes on textual and contextual analysis of the Amaq Setoweq folklore. Textual analysis covers 3 (three) language meta-fungctions where are describe into lexico-grammar structure system and the Lombok Folklore Texs entitled amaq Setoweq or âTeks Cerita Rakyat Lombok Amaq Setoweq (TCRLAS)â nonlinguistic contextual analysis. The result of the research on the lexico-grammmar structure system shows: (1) referring to the ideasional description, narrative texs dominantly use behavioral process (30,43%), material process (26%), verbal process (18,26%), mental process (20%), relational process (8,69%), form process (5,21%), (2) referring to the interpersonal process description, texs is dominated by declarative mood (62,72%), exclamation mood (32%), imperative mood (1,7%), interogative mood (3,7%), and circumstansial adjunction (68,69%), mood adjunction (4,34%), polariy adjunction (0%), comment adjunction (0,8%), vocative adjunction (0,8%), conjungtive adjunction (2,6%), and continuity adjunction (6%), (3) referring to the textual description: topical theme (56,95%), interpersonal finite theme (0%), interpersonal mood adjunction theme (26,95%), interpersonal vocative adjunction theme (2,6%), interpersonal polarity adjunction theme (0%), interpersonal comment adjunction theme (5,2%), textual continuituity adjunction theme (6,8%), and textual conjungtive adjunction theme (2,6%). The analysis of nonlinguistic context covers situasional context analysis, cultural context, idelogy context identifies the closely relation between the textual meaning which is described into lexico-grammar structure system and its clauses with lombok society in general. The clause forms a text showsthe realityu of thecultural and social condition of here inafter is related with the study of discourse analysis lecture at collage using the constructivist study method. The relevance is acceptedto relate the content and technic or how to anayzethe discourse/text by usingsystemic functional linguistics (SFL) theory interpersonal comment adjunction Keywords: Text, context, Systemic Funfcional Linguistics, Amaq Setoweq Folklore, The Theory of Constructivist Study